Implementation of a Research-oriented Model of Learning in the Subject Technique in Lower Secondary Education with a Focus on the Cognitive Domain - Ďuriš, Milan; Kvasnová, Petra (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2022)
In this paper, attention is paid to the inquiry-oriented model of students’ education in the subject Technique in lower secondary education. The proposed model reflects the long-term needs of students’ education in the subject Technique, which, in spite of the updated content of the curriculum in the Educational Standard of the subject Technique, have not yet been fulfilled. These issues are addressed within the KEGA project No. 006UMB-4/2022 in the years 2022–2024. The project is funded by the Ministry of Education and Science of the Slovak Republic. In the article we present basic information about the background, objectives, about the research team and the planned outputs of the problem.